Beyond Cortés and Montezuma: the conquest of Mexico revisited - Huber, Vitus, editor; Schwaller, John F., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2025)
Beyond Cortés and Montezuma explores the conquest of Mexico from a nuanced perspective that reflects upon prior works in the field. The book analyzes the semantics of conquest, Nahua history keeping, power dynamics, and artistic and narrative representations.--Provided by publisher.
Language of "conquest" in colonial Nahuatl manuscripts / Stephanie Wood -- "Perpetuating lands": the crucial transition from war to colonial settlement in the Conquista of Mexico / Vitus Huber -- The Conquista of Mexico today: hyperactive memory, national identity, and symbolic violence / Justyna Olko -- The last journey of Cuauhtemoc: models for the Anales de Tlatelolco's version of Cuauhtemoc's death / Julia Madajczak -- Zacarías de Santiago: a Tlaxcalteca conquistador in the evolution of Nahua historical memories / Robert Haskett -- How to read native accounts of the Conquista of Mexico / María Castañeda de la Paz -- Moteuczoma's surrender of power: a critical proposal / Miguel Pastrana Flores -- The forty teteuctin: Nahua bodies in the Mediterranean / Erika Escutia -- Beyond Malinche: other native women in the Conquista / Lori Boornazian Diel -- Between victor and vanquished: the metamorphosis of Moteuczoma in a painted biombo / Patrick Hajovsky.
Keywords: Nahuas -- Mexico -- History; Mexico -- History -- Conquest, 1519-1540 -- Historiography; Mexico -- History -- Conquest, 1519-1540 -- Sources